Multiple Rectangular Slotted Patch Antenna with Roof-top Shaped at 15.3 GHz - Melis Ecem Koca; Tahsin Durak; S. Taha Imeci, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a compact sized, high frequency microstrip patch antenna with probe feeding is designed, simulated, built and tested. The patch of the antenna is diamond shaped which has a rectangular slot in the upper-center. Main contribution of the paper is to perturb the side edges of the patch and to add a rectangular slot. Parametric study of that twosubstrate change was investigated. The proposed structures were simulated by using the Sonnet Suites, a planar 3-D electromagnetic simulation software which gave S11 value of -13.82 dB and gain value of 6.33 dB at 15.3 GHz.